Quantum dot detector and preparation method thereof

By setting the hydrophilic layer WOx on the surface of C60 and revolvingly deposition of water and Sn sources, the problem of low quality of electron transport layer in quantum dot detectors is solved, and the detection performance and stability are significantly improved.

CN119815973AActive Publication Date: 2025-04-11HUAZHONG UNIV OF SCI & TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510031569.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

During the deposition process, the existing quantum dot detectors cannot evenly and densely arrange the water source due to the hydrophobicity of the C60 material, which affects the quality of the electron transport layer and thus reduces the detection performance.

Method used

A hydrophilic layer material WOx is provided on the surface of C60, and an n-type electron transport layer is prepared by cyclic alternating deposition of H2O and Sn sources to improve the uniformity and density of the deposited film.

Benefits of technology

By setting up a hydrophilic layer, the quality of the n-type electron transport layer is significantly improved, the detection performance of the detector is improved, and the stability of the device is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119815973A_ABST
    Figure CN119815973A_ABST
Patent Text Reader

Abstract

The invention provides a quantum dot detector and a preparation method of the quantum dot detector, and the preparation method of the quantum dot detector comprises the steps: sequentially preparing a bottom electrode, an electron blocking layer, a P-type hole transport layer, a light absorption layer and a sacrificial layer on a substrate; preparing a hydrophilic layer on the surface of one side of the sacrificial layer; the material of the hydrophilic layer is WOx; and preparing an n-type electron transport layer on the surface of one side of the hydrophilic layer, and preparing a top electrode on the surface of one side, far away from the hydrophilic layer, of the n-type electron transport layer. According to the scheme, the hydrophilic layer is arranged on the surface of the sacrificial layer C60, and after a water source is deposited on the hydrophilic layer, the contact angle can be greatly reduced (according to an experimental result, the contact angle of water is 6 degrees), so that the quality of the n-type electron transport layer can be improved, and the detection performance of the detector can be integrally improved; the introduction of the tungsten oxide interface layer and the improvement of the quality of the electron transport layer can inhibit the migration of halide ions (I-) to a certain extent, and improve the stability of the device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of infrared detection technology, and in particular to a quantum dot detector and a method for preparing the quantum dot detector. Background Art

[0002] Infrared light is a form of electromagnetic radiation that is ubiquitous in natural and artificial environments. Infrared imaging technology has greater application potential in emerging fields such as intelligent sensing, machine vision, and autonomous driving. However, infrared light cannot be directly perceived by the naked eye. Therefore, infrared photodetectors were invented to detect infrared light, and photoactive materials play a vital role in this process, among which semiconductor materials are usually used. Commercial infrared photodetectors are usually made of traditional narrow-bandgap bulk inorganic semiconductors (such as InSb, Ge, HgCdTe, InGaAs). However, bulk semiconductor materials are quite limited. First, they are usually grown under extreme temperature and vacuum conditions, which is very costly. Second, the epitaxial growth method commonly used is epitaxial growth on a lattice-matched crystal substrate, which makes this type of infrared photodetector expensive, inflexible, and limited. Therefore, there is an urgent need for alternative materials for infrared detectors with small size, low dark current, and low energy consumption.

[0003] Compared with traditional bulk semiconductors, infrared quantum dots have the advantages of easy processing, good flexibility and photostability, and high absorption coefficient. Colloidal photodetectors have the advantages of adjustable corresponding bands, excellent detection performance, low price, and process compatibility. They have shown great potential to replace silicon-based pixel arrays and achieve full coverage imaging in the short-wave infrared band.

[0004] However, existing quantum dot detectors are atomically deposited on C 60 The surface is deposited by first water source and then tin source. The known quality is the best, but C 60 The material is hydrophobic, which means that the water source cannot be evenly and densely laid on C 60 The surface will cause the SnOx deposition quality to be very low in the first few (dozen) cycles, and the defects produced will affect the overall quality of the electron transport layer, thus having a negative impact on the detection performance of the detector.

[0005] Application Contents

[0006] In view of the above problems, the present application provides a quantum dot detector and a method for preparing the quantum dot detector, which improves the quality of the n-type electron transport layer, improves the overall detection performance of the detector, and improves the stability of the device.

[0007] In a first aspect, a method for preparing a quantum dot detector is provided, comprising:

[0008] providing a substrate;

[0009] Sequentially preparing a bottom electrode, an electron blocking layer, a P-type hole transport layer, a light absorbing layer, and a sacrificial layer on the substrate;

[0010] A hydrophilic layer is prepared on a surface of the sacrificial layer away from the substrate; the hydrophilic layer is made of WOx;

[0011] An n-type electron transport layer is prepared on a surface of the hydrophilic layer away from the sacrificial layer, wherein the hydrophilic layer is used to improve the uniformity and compactness of the n-type electron transport layer;

[0012] A top electrode is prepared on a surface of the n-type electron transport layer away from the hydrophilic layer.

[0013] In one embodiment, the step of preparing an n-type electron transport layer on a surface of the hydrophilic layer away from the sacrificial layer comprises:

[0014] H2O and Sn source are cyclically and alternately deposited on the hydrophilic layer to prepare the n-type electron transport layer.

[0015] In one embodiment, the hydrophilic layer material is WO3.

[0016] In one embodiment, a hydrophilic layer is prepared on a surface of the sacrificial layer away from the substrate, comprising:

[0017] The tungsten boat is heated by thermal evaporation to form a WOx film on a surface of the sacrificial layer away from the substrate;

[0018] The thermal evaporation rate is 0.001-0.003 nm / s, and the thickness of the WOx film is 1-1.5 nm.

[0019] In one embodiment, the tungsten boat is heated by thermal evaporation to form a WOx film on a surface of the sacrificial layer away from the substrate, and then the following steps are further included:

[0020] The WOx film is plasma cleaned.

[0021] In one embodiment, HO and Sn sources are cyclically and alternately deposited on the hydrophilic layer to prepare the n-type electron transport layer, comprising:

[0022] The n-type electron transport layer is prepared by using atomic layer deposition (ALD) with TDMASn (tetrakis(dimethylamino)tin) as a Sn source, and cyclically and alternately depositing H2O and Sn sources on the hydrophilic layer to obtain a SnO2 film.

[0023] In one embodiment, the material of the bottom electrode and the top electrode is ITO;

[0024] The material of the electron blocking layer is NiO X ;

[0025] The material of the P-type hole transport layer is PbS-EDT;

[0026] The material of the light absorbing layer is PbS-I / Br;

[0027] The material of the sacrificial layer is C 60 .

[0028] In a second aspect, the present application provides a quantum dot detector, which includes, from bottom to top, a bottom electrode, an electron blocking layer, a P-type hole transport layer, a light absorbing layer, a sacrificial layer, a hydrophilic layer, an n-type electron transport layer, and a top electrode;

[0029] Wherein, the hydrophilic layer material is WOx, which is used to improve the uniformity and compactness of the n-type electron transport layer.

[0030] In one embodiment, the hydrophilic layer material is WO3.

[0031] In one embodiment, the material of the bottom electrode and the top electrode is ITO;

[0032] The material of the electron blocking layer is NiO X ;

[0033] The material of the P-type hole transport layer is PbS-EDT;

[0034] The material of the light absorbing layer is PbS-I / Br;

[0035] The material of the sacrificial layer is C 60 .

[0036] The solution of this application is in the sacrificial layer C 60 A hydrophilic layer made of WOx is set on the surface, and then H2O and Sn sources are cyclically and alternately deposited (H2O is deposited first) on the hydrophilic layer. After the water source is deposited on the hydrophilic layer, the contact angle of water will be greatly reduced (according to experimental results, the contact angle of water is 6°), which will improve the uniformity and density of the atomic layer deposition film, thereby improving the quality of the n-type electron transport layer and improving the detection performance of the detector as a whole.

[0037] In addition, a hydrophilic layer is set, and its material is WOx, which is extremely hydrophilic and has a large number of hydroxyl groups on the surface, which is conducive to the deposition and close packing of water sources. The deposited film can maintain a high uniformity and density during the entire cycle process, which can effectively improve the transmission performance of the electron transport layer, thereby improving the detection performance of the device. In addition, the introduction of the tungsten oxide interface layer and the improvement of the quality of the electron transport layer can inhibit the migration of halogen ions (I-) to a certain extent and improve the stability of the device.

[0038] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Also, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:

[0040] Figure 1 It is a schematic diagram of a process of an embodiment of a method for preparing a quantum dot detector of the present application;

[0041] Figure 2a Schematic diagram of the contact angle of water after the water source is deposited during the atomic layer deposition process when preparing the n-type electron transport layer without setting the hydrophilic layer

[0042] Figure 2b This is a schematic diagram of the contact angle of water after a water source is deposited during atomic layer deposition when a hydrophilic layer is provided in the present application to prepare an n-type electron transport layer;

[0043] Figure 3 It is a schematic structural diagram of an embodiment of a quantum dot detector of the present application. DETAILED DESCRIPTION

[0044] Exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present disclosure and to be able to fully convey the scope of the present disclosure to those skilled in the art. In addition, in the following description, descriptions of well-known structures and technologies are omitted to avoid unnecessary confusion of the concepts of the present disclosure.

[0045] Various structural schematic diagrams according to embodiments of the present disclosure are shown in the accompanying drawings. These figures are not drawn to scale, and some details are magnified and some details may be omitted for the purpose of clear expression. The shapes of various regions and layers shown in the figures and the relative sizes and positional relationships therebetween are only exemplary, and may deviate in practice due to manufacturing tolerances or technical limitations, and those skilled in the art may further design regions / layers with different shapes, sizes, and relative positions according to actual needs.

[0046] The quantum dot detector of the present application is described in detail below with reference to the accompanying drawings.

[0047] See also Figure 1 , Figure 1 The present invention is a schematic flow chart of an embodiment of a method for preparing a quantum dot detector of the present invention, which is characterized by comprising:

[0048] Step S11: providing a substrate.

[0049] The substrate material may be a glass substrate.

[0050] Step S12: preparing a bottom electrode, an electron blocking layer, a P-type hole transport layer, a light absorbing layer, and a sacrificial layer in sequence on the substrate.

[0051] In one embodiment, the bottom electrode layer material is indium tin oxide ITO. Specifically, an indium tin oxide film is sputtered on a substrate by a magnetron sputtering method, and the indium tin oxide film is patterned by a laser etching / photolithography / nanoimprinting process to form a bottom electrode. After the bottom electrode is prepared, the bottom electrode layer can be further cleaned, for example, by sequentially using pure water, ethanol, and N,N-dimethylformamide solution DMF to clean the bottom electrode layer.

[0052] An electron blocking layer is provided on the bottom electrode. The material of the electron blocking layer is NiOx. On the bottom electrode layer, vacuum magnetron sputtering of NiO target material for Li is performed to prepare the electron blocking layer. Specifically, the distance between the target and the substrate is set to 80cm, and sputtering is performed in radio frequency mode. Argon gas is introduced to make the chamber pressure about 2.0Pa, the sputtering power is 100-200W, and the sputtering time is 3-20min, so as to obtain a NiOx film of about 20nm thickness, thereby forming an electron blocking layer.

[0053] A P-type hole transport layer is arranged on the electron blocking layer. The material of the P-type layer is PbS, and specifically, the material of the P-type layer is PbS-EDT (PbS passivated with ethanedithiol ligand). In one embodiment, the operation is carried out in a fume hood, PbS CQD (colloidal quantum dots) with an absorption peak of 880 nm is dissolved in n-octane to prepare a 40 mg / ml quantum dot solution, and EDT solution is dispersed in acetonitrile to prepare a ligand solution with an EDT mass fraction of 0.01%. A solid phase exchange method is used to first spin-coat a layer of quantum dot solution (spin coating speed is 2500-5000 r / min, for example, 4000 r / min, spin coating acceleration is 500-2000 r / s, spin coating time is 10-30s, for example, 20s), and then the ligand solution is dripped onto the quantum dot solution film, and the film is left to stand for 30s to wait for the ligand exchange to be complete, and then the surface is washed twice with acetonitrile to obtain a PbS-EDT film with a thickness of about 20 nm, thereby obtaining a P-type hole transport layer.

[0054] A light absorbing layer is prepared on the P-type hole transport layer, and the material of the light absorbing layer is PbS-I / Br (halogen ion passivated PbS). The specific preparation method of the light absorbing layer includes:

[0055] 1) The PbS colloidal quantum dots used in the preparation of the photodetector light-absorbing layer are synthesized by cation exchange. Specifically, thioacetamide is used as a sulfur source and zinc stearate is used as a zinc source to synthesize zinc sulfide quantum dots, and then lead chloride is used as a lead source to perform cation exchange, and the absorption peak of PbS CQD is controlled by controlling the reaction time. The PbS CQD synthesized by this method is wrapped with oleic acid ligands, and the spacing between quantum dots is too large, resulting in a low mobility problem. Therefore, it is necessary to perform ligand exchange on it, replacing the long-chain oleic acid ligands with short-chain iodine and bromine single-atom ligands to enhance the electrical properties of PbS CQD.

[0056] 2) Ligand exchange was carried out in a nitrogen atmosphere glove box, specifically: PbSCQD synthesized by cation exchange method was dissolved in n-octane at a concentration of 10 mg / ml to obtain a quantum dot solution for use. PbI2 and PbBr2 solid drugs were weighed on a balance and mixed with N, N-dimethylformamide (DMF) solution, fully shaken and dissolved, and configured into ligand solutions with PbI2 and PbBr2 concentrations of 0.0267mmol / ml and 0.0115mmol / ml, respectively. Use a syringe and a filter head with a pore size of 0.22μm to filter and mix the quantum dot solution and the ligand solution in a volume ratio of 1:1, shaken fully, and ligand exchange was performed. After standing, the PbS CQD with iodine and bromine atom ligands was in the lower DMF polar phase, and the n-octane solvent on the upper layer became transparent, and the upper solution was removed. In order to reduce the content of residual oleic acid, an equal amount of n-octane was added, mixed and shaken for cleaning, and the upper liquid was removed after stratification. The cleaning process was repeated twice. Finally, the lower layer of DMF solution containing PbS CQD was divided into centrifuge tubes and centrifuged at 9000r / min for 3min. After centrifugation, the solution was removed and the residual precipitate was the PbS CQD wrapped with iodine and bromine atom ligands, which was placed in a low-pressure drying oven to further remove the residual solvent for use.

[0057] 3) The dried PbS CQD quantum dot solid is added to the existing quaternary dispersion system (DMF:DMSO:BTA:3-pyridinemethylamine = 350ul:250ul:370ul:30ul) with a concentration of 400mg / ml, and the film is coated after sufficient oscillation and dispersion at a speed of 2500r / min for 40s to obtain a PbS-I / Br film with a thickness of about 250nm, thereby preparing a light absorbing layer.

[0058] A sacrificial layer is prepared on the light absorbing layer, wherein the material of the sacrificial layer is C 60The device with the light-absorbing layer was placed on a thermal evaporation instrument and coated by thermal evaporation. The tungsten boat was heated to C 60 , maintaining the evaporation rate at 0.005-0.015 nm / s, preparing a C layer with a thickness of about 10-40 nm, for example, 15 nm 60 , a sacrificial layer is prepared.

[0059] Step S13: preparing a hydrophilic layer on the surface of the sacrificial layer away from the substrate; the material of the hydrophilic layer is WOx.

[0060] In one embodiment, a tungsten boat is heated by thermal evaporation to form a WOx film on the surface of the sacrificial layer away from the substrate, wherein the thermal evaporation rate is 0.001-0.003 nm / s, and the thickness of the WOx film is 1-1.5 nm. Furthermore, the WOx film is plasma cleaned to further improve its hydroxylation level.

[0061] In one embodiment, the hydrophilic layer material is WO3.

[0062] Step S14: preparing an n-type electron transport layer on a surface of the hydrophilic layer away from the sacrificial layer, wherein the hydrophilic layer is used to improve the uniformity and compactness of the n-type electron transport layer.

[0063] H2O and Sn sources are cyclically and alternately deposited on the hydrophilic layer to prepare the n-type electron transport layer. Specifically, atomic layer deposition is adopted, TDMASn (tetrakis(dimethylamino)tin) is used as the Sn source, and H2O and Sn sources are cyclically and alternately deposited on the hydrophilic layer to obtain a SnO2 film to prepare the n-type electron transport layer. During atomic layer deposition, the tin source temperature is set to 60°C and the substrate temperature is set to 90°C to try to make the reaction proceed fully. After 250 cycles of growth, a SnO2 film with a thickness of about 40nm is obtained, thereby obtaining an n-type electron transport layer.

[0064] Please combine Figure 2a-2b , it was found through experiments that the sacrificial layer C 60 It is a hydrophobic material. During atomic layer deposition, H2O and Sn sources are alternately deposited (H2O is deposited first) on C 60 This will cause the water source to not be evenly and densely laid on C 60 On the surface, Figure 2a As shown, the water source is deposited in C 60 When the surface is exposed to the air, a large contact angle will be generated (according to experimental results, the contact angle of water is 91.8°), which will lead to a very low quality of the n-type electron transport layer finally deposited. The defects generated affect the overall quality of the n-type electron transport layer, thereby having a negative impact on the detection performance of the detector. 60A hydrophilic layer is set on the surface, and its material is WOx, and then H2O and Sn sources are alternately deposited on the hydrophilic layer (H2O is deposited first), such as Figure 2b As shown, after the water source is deposited on the hydrophilic layer, the contact angle of water will be greatly reduced (according to the experimental results, the contact angle of water is 6°), which will improve the uniformity and density of the atomic layer deposition film, thereby improving the quality of the n-type electron transport layer and improving the detection performance of the detector as a whole.

[0065] In addition, a hydrophilic layer is set, and its material is WOx, which is extremely hydrophilic and has a large number of hydroxyl groups on the surface, which is conducive to the deposition and close packing of water sources. The deposited film can maintain a high uniformity and density during the entire cycle process, which can effectively improve the transmission performance of the electron transport layer, thereby improving the detection performance of the device. In addition, the introduction of the tungsten oxide interface layer and the improvement of the quality of the electron transport layer can inhibit the migration of halogen ions (I-) to a certain extent and improve the stability of the device.

[0066] Step S15: preparing a top electrode on a surface of the n-type electron transport layer away from the hydrophilic layer.

[0067] The material of the top electrode is indium tin oxide ITO. The top electrode is coated by magnetron sputtering, and the target material is indium-doped tin oxide. The sputtering power is 100w-200w, and the sputtering time is 10-30 minutes.

[0068] See also Figure 3 , Figure 3 This is a schematic diagram of the structure of an embodiment of the quantum dot detector of the present application. The quantum dot detector specifically includes: from bottom to top, it includes a bottom electrode 111, an electron blocking layer 112, a p-type hole transport layer 113, a light absorbing layer 114, a sacrificial layer 115, a hydrophilic layer 118, an n-type electron transport layer 116, and a top electrode 117. Among them, the electron blocking layer 112 is arranged on the bottom electrode 111; the p-type hole transport layer 113 is arranged on the side of the electron blocking layer 112 away from the bottom electrode 111; the light absorbing layer 114 is arranged on the side of the p-type hole transport layer 113 away from the bottom electrode 111; among them, the sacrificial layer 115 is arranged on the side of the light absorbing layer 114 away from the bottom electrode 111; the n-type electron transport layer 116 is arranged on the side of the sacrificial layer 115 away from the bottom electrode 111; and the top electrode 117 is arranged on the side of the n-type electron transport layer 116 away from the bottom electrode 111.

[0069] The material of the bottom electrode 111 is the same as that of the top electrode 117 , both of which are indium tin oxide thin films.

[0070] The material of the n-type electron transport layer 116 is SnO 2 .

[0071] The material of the sacrificial layer 115 is C60 .

[0072] Wherein, the material of the P-type hole transport layer is PbS-EDT (PbS passivated with ethanedithiol ligand);

[0073] The material of the light absorbing layer 114 is PbS-I / Br (halogen ion passivated PbS), which can absorb the energy of photons under 1550nm light irradiation to generate light signals. The electron blocking layer 112, the p-type hole transport layer 113, the light absorbing layer 114, the sacrificial layer 115, and the n-type electron transport layer 116 form an ohmic contact between the bottom electrode 111 and the top electrode 117. Among them, the electron blocking layer 112, the p-type hole transport layer 113, the light absorbing layer 114, the sacrificial layer 115, and the n-type electron transport layer 116 form a pin structure as a whole. Under 1550nm light irradiation, the light absorbing layer 114 will generate electrons and vacancies, and the electrons will go along the sacrificial layer 115 to the n-type electron transport layer 116; the vacancies will reach the p-type hole transport layer 113. The electron blocking layer 112 prevents electrons from the light absorbing layer 114 from traveling back to the p-type hole transport layer 113. The p-type hole transport layer 113 and the n-type electron transport layer 116 form a pn junction (light-emitting diode structure). The p-type hole transport layer 113 generates carriers. As the bias voltage increases, the built-in potential of the initial built-in electric field begins to change. When the p-type hole transport layer 113 is completely exhausted, the photocurrent is maximum. The initial dark current is subtracted from the photocurrent to obtain the net photocurrent. The optical signal per unit area is the responsivity of 1550nm light.

[0074] In the present application, the hydrophilic layer material is WOx, which is used to improve the uniformity and compactness of the n-type electron transport layer. Specifically, the hydrophilic layer material is WO3.

[0075] It was found through experiments that the sacrificial layer C 60 It is a hydrophobic material. During atomic layer deposition, H2O and Sn sources are alternately deposited (H2O is deposited first) on C 60 This will cause the water source to not be evenly and densely laid on C 60 On the surface, Figure 2a As shown, the water source is deposited in C 60 When the surface is exposed to the air, a large contact angle will be generated (according to experimental results, the contact angle of water is 91.8°), which will lead to a very low quality of the n-type electron transport layer finally deposited. The defects generated affect the overall quality of the n-type electron transport layer, thereby having a negative impact on the detection performance of the detector. 60 A hydrophilic layer is set on the surface, and its material is WOx, and then H2O and Sn sources are alternately deposited on the hydrophilic layer (H2O is deposited first), such as Figure 2bAs shown, after the water source is deposited on the hydrophilic layer, the contact angle will be greatly reduced (according to the experimental results, the contact angle of water is 6°), which will improve the uniformity and density of the atomic layer deposition film, thereby improving the quality of the n-type electron transport layer and improving the detection performance of the detector as a whole.

[0076] In addition, a hydrophilic layer is set, and its material is WOx, which is extremely hydrophilic and is conducive to the deposition and close arrangement of water sources. The entire cycle process can maintain a high uniformity and density, which can effectively improve the transmission performance of the electron transport layer, thereby improving the detection performance of the device. In addition, the introduction of the tungsten oxide interface layer and the improvement of the quality of the electron transport layer can inhibit the migration of halogen ions (I-) to a certain extent and improve the stability of the device.

[0077] The algorithm and display provided herein are not inherently related to any particular computer, virtual system or other device. Various general purpose systems can also be used together with the teachings based on this. According to the above description, it is obvious that the structure required for constructing such systems. In addition, the application is not directed to any specific programming language either. It should be understood that various programming languages ​​can be utilized to realize the content of the application described herein, and the description of the specific language above is for the purpose of disclosing the best mode of implementation of the application.

[0078] In the description provided herein, a large number of specific details are described. However, it is understood that the embodiments of the present application can be practiced without these specific details. In some instances, well-known methods, structures and techniques are not shown in detail so as not to obscure the understanding of this description.

[0079] Similarly, it should be understood that in order to streamline the present disclosure and assist in understanding one or more of the various aspects of the application, in the above description of exemplary embodiments of the present application, the various features of the present application are sometimes grouped together into a single embodiment, figure, or description thereof.

[0080] Those skilled in the art will appreciate that the modules in the device in the embodiment can be adaptively changed and arranged in one or more devices different from the embodiment. The modules or units or components in the embodiment can be combined into one module or unit or component, and in addition they can be divided into multiple submodules or subunits or subcomponents. Except that at least some of such features and / or processes or units are mutually exclusive, all features disclosed in this specification (including abstracts and drawings) and all processes or units of any method or device disclosed in this manner can be combined in any combination. Unless otherwise explicitly stated, each feature disclosed in this specification (including accompanying abstracts and drawings) can be replaced by alternative features that provide the same, equivalent or similar purposes.

[0081] Furthermore, those skilled in the art will appreciate that although some embodiments herein include certain features included in other embodiments but not other features, the combination of features from different embodiments is meant to be within the scope of the present application and to form different embodiments.

[0082] It should be noted that the above embodiments illustrate the present application rather than limit the present application. Any reference symbol between brackets should not be constructed as a limitation to the present application. The word "comprising" does not exclude the existence of components or steps not listed in the present application. The word "one" or "an" before a component does not exclude the existence of multiple such components. The present application can be implemented by means of hardware including several different components and by means of a suitably programmed computer. In the embodiments in which several devices are listed, several of these devices can be embodied by the same hardware item. The use of the words first, second, and third, etc. does not indicate any order. These words can be interpreted as names.

Claims

1. A method for preparing a quantum dot detector, characterized in that: include: providing a substrate; Sequentially preparing a bottom electrode, an electron blocking layer, a P-type hole transport layer, a light absorbing layer, and a sacrificial layer on the substrate; A hydrophilic layer is prepared on a surface of the sacrificial layer away from the substrate; the hydrophilic layer is made of WOx; An n-type electron transport layer is prepared on a surface of the hydrophilic layer away from the sacrificial layer, wherein the hydrophilic layer is used to improve the uniformity and compactness of the n-type electron transport layer; A top electrode is prepared on a surface of the n-type electron transport layer away from the hydrophilic layer.

2. The preparation method according to claim 1, characterized in that: The step of preparing an n-type electron transport layer on a surface of the hydrophilic layer away from the sacrificial layer comprises: H2O and Sn source are cyclically and alternately deposited on the hydrophilic layer to prepare the n-type electron transport layer.

3. The preparation method according to claim 1, characterized in that: The hydrophilic layer material is WO3.

4. The preparation method according to claim 1, characterized in that: The step of preparing a hydrophilic layer on a surface of the sacrificial layer away from the substrate comprises: The tungsten boat is heated by thermal evaporation to form a WOx film on a surface of the sacrificial layer away from the substrate; The thermal evaporation rate is 0.001-0.003 nm / s, and the thickness of the WOx film is 1-1.5 nm.

5. The preparation method according to claim 4, characterized in that: The tungsten boat is heated by thermal evaporation to form a WOx film on a surface of the sacrificial layer away from the substrate, and then the method further includes: The WOx film is plasma cleaned.

6. The preparation method according to claim 2, characterized in that: The n-type electron transport layer is prepared by cyclically and alternately depositing H2O and Sn source on the hydrophilic layer, comprising: The n-type electron transport layer is prepared by using atomic layer deposition (ALD) with TDMASn (tetrakis(dimethylamino)tin) as a Sn source, and cyclically and alternately depositing H2O and Sn sources on the hydrophilic layer to obtain a SnO2 film.

7. The preparation method according to claim 1, characterized in that: The material of the bottom electrode and the top electrode is ITO; The material of the electron blocking layer is NiO X ; The material of the P-type hole transport layer is PbS-EDT; The material of the light absorbing layer is PbS-I / Br; The material of the sacrificial layer is C 60 .

8. A quantum dot detector, characterized in that: The quantum dot detector includes, from bottom to top, a bottom electrode, an electron blocking layer, a P-type hole transport layer, a light absorbing layer, a sacrificial layer, a hydrophilic layer, an n-type electron transport layer and a top electrode; Wherein, the hydrophilic layer material is WOx, which is used to improve the uniformity and compactness of the n-type electron transport layer.

9. The quantum dot detector according to claim 8, characterized in that: The hydrophilic layer material is WO3.

10. The quantum dot detector according to claim 8, characterized in that: The material of the bottom electrode and the top electrode is ITO; The material of the electron blocking layer is NiO X ; The material of the P-type hole transport layer is PbS-EDT; The material of the light absorbing layer is PbS-I / Br; The material of the sacrificial layer is C 60 .

Citation Information

Patent Citations

  • Quantum dot photoelectric detector and preparation method thereof

    CN115117245A

  • Nanostructured Inorganic-Organic Heterojunction Solar Cells and Fabrication Method Thereof

    KR101116250B1

  • Selective High-K dielectric film deposition for semiconductor device

    US20090272965A1

  • Manganese oxide film forming method

    US20140363971A1